Salt Bridge Rearrangement (SaBRe) Explains the Dissociation Behavior of Noncovalent Complexes - Ogorzalek Loo, Rachel R. (J Am Soc Mass Spectrom, 2016)
Native electrospray ionization-mass spectrometry, with gas phase activation and solution compositions that partially release subcomplexes, can elucidate topologies of macromolecular assemblies. That so much complexity can be preserved in gas phase assemblies is remarkable, although a long-standing conundrum has been the differences between their gas and solution phase decompositions. Collision-induced dissociation of multimeric noncovalent complexes typically distributes products asymmetrically; i.e., by ejecting a single subunit bearing a large percentage of the excess charge. That unexpected behavior has been rationalized as one subunit “unfolding” to depart with more charge. We present an alternative explanation based on heterolytic ion-pair scission and rearrangement, [Formula: see text] a mechanism that inherently partitions charge asymmetrically. Excessive barriers to dissociation are circumvented in this manner, when local charge rearrangements access a lower-barrier surface. An implication of this ion pair consideration is that stability differences between high- and low-charge state ions usually attributed to Coulomb repulsion may, alternatively, be conveyed by attractive forces from ion pairs (salt bridges) stabilizing low-charge state ions. Should the number of ion pairs be roughly inversely related to charge, symmetric dissociations would be favored from highly charged complexes, as observed. Correlations between a gas phase protein’s size and charge reflect the quantity of restraining ion pairs. Collisionally-facilitated salt bridge rearrangement (SaBRe) may explain unusual size “contractions” seen for some activated, low charge state complexes. That some low-charged multimers preferentially cleave covalent bonds or shed small ions to disrupting noncovalent associations is also explained by greater ion pairing in low charge state complexes.